Microwave‐Assisted Domino Heck Cyclization and Phosphorylation: Synthesis of Phosphorus Containing Heterocycles. Issue 24 (12th June 2019) - Ramesh, Karu; Satyanarayana, Gedu
Abstract : A domino [Pd]‐catalyzed intramolecular Heck cyclization followed by intermolecular phosphorylation, for the construction of phosphorus containing heterocyclic compounds, is presented. Notably, the process is accelerated by microwave heating conditions and enabled the construction of C–C and C–P bonds in short reaction times. Abstract : A domino [Pd]‐catalyzed intramolecular Heck cyclization followed by intermolecular phosphorylation, for the construction of phosphorus containing heterocyclic compounds, is presented. Notably, the process is accelerated by microwave heating conditions and enabled the construction of C–C and C–P bonds in short reaction times.